A Short History of Documentary Film - Bancos, Raluca Iulia (Acta Universitatis Danubius. Communicatio, 2022)
In the present paper, we aimed to realise a theoretical study about the story of documentary film over time. We consider this short history will be useful to specialized literature, as it helps to understand better the genre of documentary film and the influences that political changes have had over time on this genre. At the beginning, the documentary film was an experiment for those who captured scenes from everyday life. After that, it had various facets, as an ideological tool, as an informative media product, as an artistic product. Nowadays, we are talking about participatory documentary, where audience has the opportunity to co-create content with the documentary producers.